VD_FINDINFO HC / 2015 / 356 vom 7. April 2015 - VD Tribunal cantonal (2015)
REMISE CONVENTIONNELLE DE DETTE, PRINCIPE DE LA BONNE FOI, INTERPRÉTATIONSENS GÉNÉRAL | 2 CC, 115 CO, 18 al. 1 CO, 322 al. 1 CPC (CH)